Environmental analysis units and strategic decision‐making: A field study of selected ‘leading‐edge’ corporations - Lenz, R. T.; Engledow, Jack L. (Strategic Management Journal, 1986)
Abstract In response to increasing environmental change many corporations have developed specialized environmental scanning units. Previous research reveals conflicting findings regarding the viability of these units for introducing environmentally relevant information into strategic decision processes. A field study was conducted on 10 ‘leading‐edge’ corporations. The results show continuing experimentation with alternative administrative structures and the vulnerability of units that are not tightly linked with strategic planning processes.